Advances in Deep Learning for Digital Signal Processing in Coherent Optical Modems - Kuschnerov, Maxim; Schaedler, Maximilian; Bluemm, Christian; Calabro, Stefano (2020 Optical Fiber Communications Conference and Exhibition (OFC), 2020)
We analyze the advances of deep learning in optical coherent modems on the physical layer with respect to modulation design, equalization and signal detection and give an outlook on a combined control and physical layer optimization using neural networks.